TURBA SASTRAWAN LEKRA DALAM RESISTENSI KELAS PEKERJA: HISTORIOGRAFI SASTRA INDONESIA PERIODE 1960-AN - Zulfikar, Mohammad Fikri; Marwan, Iwan; Saryono, Djoko; Syahri, Mochammad (Universitas Andalas, 2023)
This study aims to describe the efforts made by the writers of the People's Cultural Institute (Lekra) in describing the resistance of the peasants and workers in their literary works so that they are better known by the wider community. Among them is using the descending method or commonly known as the abbreviation Turba to see the immediate conditions of the people from the peasants and workers' lives. This research uses a qualitative research type with a historiographical approach which is a tool in seeing the motives, types, and themes of literary works that develop in society. The data of this study refers to a group of information from text readings and historical facts. Sources of research data include the Harian People's newspaper as the primary source and other library materials as a complement. Data accessed from the collections of the H.B. Literature Documentation Center (PDS). Jassin to the Jakarta National Library (Perpusnas). The research instrument is the researcher himself (human instrument). This research yielded information about (1) the background of turba, (2) the turba method, (3) the experiences of lekra writers doing turba, and (4) the works of lekra writers which describe the resistance of the peasants and workers.